Large-size CoSbS-based thermoelectric semiconductor crystal and preparation method thereof

By adjusting the stacking method and controlling the melting temperature of the raw material particles in the pupa, the swing -melting method is used to prepare the COSBS polycrystalline raw material, and the large -sized COSBS base thermal power semiconductor crystals are used to use the melting growth method to solve High problems have realized the preparation of high -performance large -scale COSBS base heating semiconductor crystals.

CN119372787AActive Publication Date: 2025-01-28WUZHEN LABORATORY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411963312.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, when the SPS sintering method is used to prepare CoSbS-based thermoelectric semiconductors, the sulfur loss rate is high, resulting in the material performance being unable to meet the actual needs.

Method used

By adjusting the stacking method of single -quality S particles and other raw materials, the melting temperature is controlled, and the melting temperature is controlled, and the COSBS polycrystalline raw material is used to use the swing and melting legal system.

Benefits of technology

显著降低了CoSbS多晶原料的硫元素损失率,制得的大尺寸CoSbS基热电半导体晶体具有相近的电导率与SPS烧结法制成的材料相比,且尺寸大、制备方法简单,易于工业化推广。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372787A_ABST
    Figure CN119372787A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermoelectric semiconductor materials, and discloses a large-size CoSbS-based thermoelectric semiconductor crystal and a preparation method thereof.The large-size CoSbS-based thermoelectric semiconductor crystal is prepared from CoSbS polycrystalline raw materials through a melt growth method, and the CoSbS polycrystalline raw materials are prepared from elemental Co particles, elemental Sb particles and elemental S particles through swing melting at the temperature of 650-750 DEG C; placing the elementary S particles on the lower layer of the elementary Co particles and the elementary Sb particles during swinging melting; the thermoelectric semiconductor crystal is excellent in conductivity, in addition, the thermoelectric semiconductor crystal prepared by the method is large in size and simple in process, and the loss rate of the sulfur element in the CoSbS polycrystal raw material can be remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric semiconductor materials, and in particular to a large-size CoSbS-based thermoelectric semiconductor crystal and a preparation method thereof. Background Art

[0002] Traditional thermoelectric semiconductor materials are mainly Bi 2 Te 3 Based thermoelectric materials and PbTe-based thermoelectric materials, but the constituent elements of the above two materials are scarce in the earth's crust and the raw materials and products are toxic. Therefore, it is of great significance to find an environmentally friendly, low-toxic thermoelectric semiconductor material with a wide range of raw materials.

[0003] The energy conversion efficiency of thermoelectric conversion technology is measured by the thermoelectric performance of the material. People usually use the thermoelectric figure of merit ZT to characterize the level of thermoelectric performance. The ZT value of thermoelectric materials can be expressed as ZT = S 2 σT / κ, where S is the Seebeck coefficient of the material, σ is the electrical conductivity of the material, T is the absolute temperature, and κ is the total thermal conductivity of the material. CoSbS has a high power factor and good mechanical stability. Electronic structure calculations show that the high power factor of CoSbS comes from the multi-valley characteristics of its energy band dispersion at the top of the valence band and the bottom of the conduction band. Doping can effectively improve the carrier concentration, effective mass of state density and mobility of CoSbS-based materials. In addition, the structure of CoSbS-based materials is a mineral resource with rich reserves, wide sources, and green environmental protection. Therefore, CoSbS-based materials are a very potential medium and high temperature thermoelectric semiconductor material.

[0004] At present, the conventional CoSbS is prepared by a pressure sintering method (SPS sintering method), such as a preparation method of a cubic CoSbS thermoelectric compound disclosed in CN109626446B, in which Co, Sb, and S powders are pressed into blocks and then sintered at high temperature to prepare a CoSbS thermoelectric compound. For example, the reference SS Zhang, Enhanced thermoelectric performance of CoSbS 0.85 Se 0.15 by point defect, Rare met.37 (2017)326-332》 discloses a CoSbS thermoelectric compound, which is prepared by an SPS sintering method. The present invention found that when the pressed raw material is placed at a temperature of 950-1150 ° C for high temperature sintering, the S element therein will be gasified, resulting in a significant increase in the loss rate of sulfur element, resulting in the performance of the prepared CoSbS-based thermoelectric semiconductor material not meeting actual needs. Summary of the invention

[0005] In order to overcome the problem of high sulfur loss rate when using the SPS sintering method to prepare CoSbS-based thermoelectric semiconductor crystals in the prior art, the present invention provides a large-sized CoSbS-based thermoelectric semiconductor crystal and a preparation method thereof. The present invention significantly reduces the sulfur loss rate of the prepared CoSbS polycrystalline raw material by adjusting the stacking method of single-substance S particles and other raw material single-substance particles in a crucible and controlling the melting temperature. The present invention also performs crystal growth on the CoSbS polycrystalline raw material by a melt growth method to prepare a large-sized CoSbS-based thermoelectric semiconductor crystal. The semiconductor crystal has a similar electrical conductivity to that of the semiconductor crystal prepared by the SPS sintering method.

[0006] The specific technical scheme of the present invention is: A large-sized CoSbS-based thermoelectric semiconductor crystal is prepared by a melt growth method using a CoSbS polycrystalline raw material. The CoSbS polycrystalline raw material is prepared by swing melting single-substance Co particles, single-substance Sb particles and single-substance S particles at 650-750°C. During the swing melting, the single-substance S particles are placed under the single-substance Co particles and the single-substance Sb particles.

[0007] Preferably, the large-sized CoSbS-based thermoelectric semiconductor crystal further includes a doping element, wherein the doping element is one of Cu, Zn, Ni and Se elements, and the doping content is 0-0.2.

[0008] Preferably, the large-sized CoSbS-based thermoelectric semiconductor crystal has a diameter of 10-40 mm and a length of 5-10 cm.

[0009] The invention provides a large-sized CoSbS-based thermoelectric semiconductor crystal. The semiconductor crystal has a large size, a simple preparation method, and is easy to industrialize. Compared with a semiconductor crystal prepared by an SPS sintering method, the semiconductor crystal has higher electrical conductivity and better thermoelectric conversion performance. The large-sized CoSbS-based thermoelectric semiconductor crystal of the invention adopts single-substance Co particles, single-substance Sb particles, and single-substance S particles as raw materials to carry out swing melting to prepare CoSbS polycrystalline raw materials, and then uses the CoSbS polycrystalline raw materials to carry out melt growth to prepare the large-sized CoSbS-based thermoelectric semiconductor crystal. The invention significantly reduces the sulfur element loss rate of the CoSbS polycrystalline raw materials by adjusting the stacking mode of the single-substance S particles and other raw material single-substance particles in a crucible and controlling the melting temperature, thereby ensuring that the required large-sized CoSbS-based thermoelectric semiconductor crystal can be prepared from the subsequent CoSbS polycrystalline raw materials.

[0010] A method for preparing the above-mentioned large-sized CoSbS-based thermoelectric semiconductor crystal comprises the following steps: Step 1: placing single S particles at the bottom of the crucible, and then stacking single Co particles and single Sb particles on the upper layer of the single S particles, vacuum sealing the crucible and then swing melting to produce CoSbS polycrystalline raw materials; Step 2: Place the CoSbS polycrystalline raw material in a crucible and seal it in vacuum, and place the crucible in a vertical crystal growth device. The vertical crystal growth device is composed of a melting zone, a cooling crystallization zone and an annealing zone from top to bottom. First, place the crucible in the melting zone for melting to form a melt, then place the crucible in the cooling crystallization zone and move it for gradient cooling crystallization, and finally anneal the crucible to form a large-sized CoSbS-based thermoelectric semiconductor crystal.

[0011] Preferably, the temperature of the swing melting in step 1 is 650-750°C.

[0012] Preferably, the swing time of the swing melting in step 1 is 0.5-3 h, and the swing rate is 10-30 r / min.

[0013] Preferably, the amount of CoSbS polycrystalline raw material used in step 2 is 20-100 g.

[0014] The present invention adopts swing melting, which can make the melt after melting more evenly mixed and improve the uniformity of the CoSbS polycrystalline raw material.

[0015] Preferably, the conditions of the melting zone in step 2 are: temperature of 950-1050°C, heating rate of 1-2.5°C / min, and residence time of 8-20 h.

[0016] Preferably, the conditions of the gradient cooling crystallization zone in step 2 are: a cooling gradient of 15-25°C / cm, and a crucible moving rate of 0.2-3 mm / h.

[0017] Preferably, in step 2, the bottom of the crucible is conical, and the taper of the cone is 17-44°; the diameter of the crucible is 10-50 mm, and the length of the crucible is 20-40 cm.

[0018] The present invention also provides a method for preparing the above-mentioned large-sized CoSbS-based thermoelectric semiconductor crystal. The method grows crystals of CoSbS polycrystalline raw materials by a melt growth method. The method can produce large-sized CoSbS-based thermoelectric semiconductor crystals. The method is simple to operate and easy to promote industrialization.

[0019] Compared with the prior art, the present invention has the following technical effects: (1) The present invention significantly reduces the sulfur element loss rate of the prepared CoSbS polycrystalline raw material by adjusting the stacking method of the elemental S particles and other raw material elemental particles in the crucible and controlling the melting temperature; (2) The large-sized CoSbS-based thermoelectric semiconductor crystals prepared by the present invention have similar electrical conductivity to the CoSbS-based thermoelectric semiconductor crystals prepared by the SPS sintering method; (3) The large-sized CoSbS-based thermoelectric semiconductor crystals prepared by the present invention are large in size, simple in preparation method, and easy to promote industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the X-ray diffraction pattern of the CoSbS-based thermoelectric semiconductor crystal of Example 1.

[0021] Figure 2 Surface morphology and mapping of the CoSbS-based thermoelectric semiconductor crystal of Example 1.

[0022] Figure 3 The CoSbS of Example 2 and Comparative Example 1 0.85 Se 0.15 Schematic diagram of the relationship between the thermal conductivity of a thermoelectric semiconductor crystal and temperature. Example 2 is in the vertical axis direction, and Comparative Example 1 is prepared by the SPS sintering method (reference). DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the embodiments.

[0024] Embodiment 1: A method for preparing a large-size CoSbS-based thermoelectric semiconductor crystal comprises the following steps: Step 1: Weigh single-element Co particles, single-element Sb particles and single-element S particles in a molar ratio of 1:1:1, place the single-element S particles at the bottom of a quartz crucible, and then stack the single-element Sb particles and single-element Co particles on the single-element S particles in sequence for vacuum sealing, and vertically place the sealed quartz crucible in a rocking furnace, raise the temperature to 650 ° C and keep it warm for 1 h to completely melt the raw materials, and then rock and mix at 15 r / min for 1 h to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0025] Step 2: Take 20 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (a double-layer quartz crucible with a diameter of 10 mm, a length of 20 cm, a conical bottom, and a taper of 35°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 950 ℃, the heating rate is 1 ℃ / min, the residence time of the quartz crucible is 8 h, to ensure the melting of the melt and the stability of the solid-liquid interface, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the temperature reduction gradient of the gradient cooling zone from top to bottom is 15 ℃ / cm), and the quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 2 mm / h until all the melt is crystallized, and then the quartz crucible is moved to the annealing zone (annealing zone temperature is 500 ℃) for annealing to form a large-size CoSbS thermoelectric semiconductor crystal with a diameter of 10 mm and a length of 10 cm.

[0026] Embodiment 2: A method for preparing a large-size CoSbS-based thermoelectric semiconductor crystal comprises the following steps: Step 1: Weigh single-substance Co particles, single-substance Sb particles, single-substance S particles and single-substance Se particles in a molar ratio of 1:1:0.85:0.15, place the single-substance S particles at the bottom of a quartz crucible, and then stack the single-substance Se particles, single-substance Sb particles and single-substance Co particles on the single-substance S particles in sequence for vacuum sealing, vertically place the sealed quartz crucible in a rocking furnace, raise the temperature to 650 ° C and keep it warm for 1 h to completely melt the raw materials, then rock and mix at 10 r / min for 0.5 h to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0027] Step 2: Take 20 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (a double-layer quartz crucible with a diameter of 10 mm, a length of 20 cm, a conical bottom, and a taper of 35°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible was sealed with a hydrogen-oxygen flame; the quartz crucible was placed vertically in the melting zone of the vertical growth furnace, the temperature of the melting zone was set to 950 °C, the heating rate was 1 °C / min, and the residence time of the quartz crucible was 8 h to ensure the melting of the melt and the stability of the solid-liquid interface. The quartz crucible was then moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone was 900 °C, and the temperature gradient of the gradient cooling zone from top to bottom was 20 °C / cm), and the quartz crucible was slowly moved in the gradient cooling zone at a moving rate of 2 mm / h until all the melt was crystallized. The quartz crucible was then moved to the annealing zone (annealing zone temperature was 500 °C) for annealing to produce large-size CoSbS with a diameter of 10 mm and a length of 10 cm. 0.85 Se 0.15 Thermoelectric semiconductor crystals.

[0028] Embodiment 3: A method for preparing a large-size CoSbS-based thermoelectric semiconductor crystal comprises the following steps: Step 1: Weigh single-substance Co particles, single-substance Sb particles, single-substance S particles and single-substance Se particles in a molar ratio of 1:1:0.85:0.15, place the single-substance S particles at the bottom of a quartz crucible, and then stack the single-substance Se particles, single-substance Sb particles and single-substance Co particles on the single-substance S particles in sequence for vacuum sealing, vertically place the sealed quartz crucible in a rocking furnace, raise the temperature to 700 ° C and keep it warm for 1 h to completely melt the raw materials, then rock and mix at 20 r / min for 1 h to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0029] Step 2: Take 50 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (a double-layer quartz crucible with a diameter of 25 mm, a length of 30 cm, a conical bottom, and a taper of 40°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible was sealed with a hydrogen-oxygen flame; the quartz crucible was placed vertically in the melting zone of the vertical growth furnace, the temperature of the melting zone was set to 1000 °C, the heating rate was 1.5 °C / min, the residence time of the quartz crucible was 12 h, to ensure the melting of the melt and the stability of the solid-liquid interface, and then the quartz crucible was moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone was 900 °C, and the temperature gradient of the gradient cooling zone from top to bottom was 20 °C / cm), and the quartz crucible was slowly moved in the gradient cooling zone at a moving rate of 0.8 mm / h until all the melt was crystallized, and then the quartz crucible was moved to the annealing zone (annealing zone temperature was 500 °C) for annealing to produce a large-size CoSbS with a diameter of 25 mm and a length of 8 cm. 0.85 Se 0.15 Thermoelectric semiconductor crystals.

[0030] Embodiment 4: A method for preparing a large-size CoSbS-based thermoelectric semiconductor crystal comprises the following steps: Step 1: Weigh single-substance Co particles, single-substance Sb particles, single-substance S particles and single-substance Se particles in a molar ratio of 1:1:0.85:0.15, place the single-substance S particles at the bottom of a quartz crucible, and then stack the single-substance Se particles, single-substance Sb particles and single-substance Co particles on the single-substance S particles in sequence for vacuum sealing, vertically place the sealed quartz crucible in a rocking furnace, raise the temperature to 700 ° C and keep it warm for 1 h to completely melt the raw materials, then rock and mix at 30 r / min for 3 h to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0031] Step 2: Take 100 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (a double-layer quartz crucible with a diameter of 40 mm, a length of 40 cm, a conical bottom, and a taper of 47°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible was sealed with a hydrogen-oxygen flame; the quartz crucible was placed vertically in the melting zone of the vertical growth furnace, the temperature of the melting zone was set to 1050 °C, the heating rate was 2.5 °C / min, the residence time of the quartz crucible was 20 h, to ensure the melting of the melt and the stability of the solid-liquid interface, and then the quartz crucible was moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone was 900 °C, and the temperature gradient of the gradient cooling zone from top to bottom was 25 °C / cm), and the quartz crucible was slowly moved in the gradient cooling zone at a moving rate of 0.2 mm / h until all the melt was crystallized, and then the quartz crucible was moved to the annealing zone (annealing zone temperature was 500 °C) for annealing to produce a large-size CoSbS with a diameter of 40 mm and a length of 5 cm. 0.85 Se 0.15 Thermoelectric semiconductor crystals.

[0032] Comparative Example 1: Compared with Example 2, the comparative example 1 adopts the reference: SS Zhang, Enhanced thermoelectric performance of CoSbS 0.85 Se 0.15 Preparation of CoSbS by SPS sintering method disclosed in 0.85 Se 0.15 Thermoelectric semiconductor crystal, prepared CoSbS 0.85 Se 0.15 The thermoelectric semiconductor crystal has a diameter of 3 mm and a length of 10 cm.

[0033] Comparative Example 2: Compared with Example 1, the quartz crucible in step 2 in Comparative Example 2 is a single-layer crucible, comprising the following steps: Step 1: Weigh single-substance Co particles, single-substance Sb particles and single-substance S particles in a molar ratio of 1:1:1, stack the single-substance S particles, single-substance Sb particles and single-substance Co particles in sequence into a quartz crucible for vacuum sealing, vertically place the sealed quartz crucible into a rocking furnace, raise the temperature to 650 ° C and keep it warm for 1 hour to completely melt the raw materials, then rock and mix at 15 r / min for 1 hour to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0034] Step 2: Take 20 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a single-layer crucible with a diameter of 10 mm, a length of 20 cm, a conical bottom, and a taper of 35°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 950 ℃, the heating rate is 1 ℃ / min, and the residence time of the quartz crucible is 8 h to ensure the melting of the melt and the stability of the solid-liquid interface, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 ℃, and the temperature reduction gradient of the gradient cooling zone from top to bottom is 15 ℃ / cm), and the quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 2 mm / h until all the melt is crystallized, and then the quartz crucible is moved to the annealing zone (annealing zone temperature is 500 ℃) for annealing to form a large-size CoSbS thermoelectric semiconductor crystal.

[0035] Comparative Example 3: Compared with Example 1, the quartz crucible in step 2 of Comparative Example 3 is a flat-bottomed crucible, comprising the following steps: Step 1: Weigh single-substance Co particles, single-substance Sb particles and single-substance S particles in a molar ratio of 1:1:1, stack the single-substance S particles, single-substance Sb particles and single-substance Co particles in sequence into a quartz crucible for vacuum sealing, vertically place the sealed quartz crucible into a rocking furnace, raise the temperature to 650 ° C and keep it warm for 1 hour to completely melt the raw materials, then rock and mix at 15 r / min for 1 hour to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0036] Step 2: Take 20 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (the quartz crucible is a double-layer crucible with a diameter of 10 mm, a length of 20 cm, and a flat bottom crucible), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 950 °C, the heating rate is 1 °C / min, and the residence time of the quartz crucible is 8 h to ensure the melting of the melt and the stability of the solid-liquid interface, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 °C, and the temperature reduction gradient of the gradient cooling zone from top to bottom is 15 °C / cm), and the quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 2 mm / h until all the melt is crystallized, and then the quartz crucible is moved to the annealing zone (annealing zone temperature is 500 °C) for annealing to form a large-size CoSbS thermoelectric semiconductor crystal.

[0037] Comparative Example 4: Compared with Example 1, the temperature of the melting zone in step 2 of Comparative Example 4 is too low, and the temperature of the melting zone is 800° C., which includes the following steps: Step 1: Weigh single-substance Co particles, single-substance Sb particles and single-substance S particles in a molar ratio of 1:1:1, stack the single-substance S particles, single-substance Sb particles and single-substance Co particles in sequence into a quartz crucible for vacuum sealing, vertically place the sealed quartz crucible into a rocking furnace, raise the temperature to 650 ° C and keep it warm for 1 hour to completely melt the raw materials, then rock and mix at 15 r / min for 1 hour to fully mix the raw materials and react completely, and then cool to room temperature to obtain CoSbS polycrystalline raw materials.

[0038] Step 2: Take 20 g of the above CoSbS polycrystalline raw material and place it in a quartz crucible (a double-layer quartz crucible with a diameter of 10 mm, a length of 20 cm, a conical bottom, and a taper of 35°), and evacuate to 10 -3 Pa, filled with argon, and then evacuated to 10 -3 Pa, after three cycles, the quartz crucible is sealed with a hydrogen-oxygen flame; the quartz crucible is vertically placed in the melting zone of the vertical growth furnace, the temperature of the melting zone is set to 800 °C, the heating rate is 1 °C / min, and the residence time of the quartz crucible is 8 h to ensure the melting of the melt and the stability of the solid-liquid interface, and then the quartz crucible is moved to the gradient cooling zone below the melting zone (the temperature of the gradient cooling zone is 900 °C, and the temperature reduction gradient of the gradient cooling zone from top to bottom is 15 °C / cm), and the quartz crucible is slowly moved in the gradient cooling zone at a moving rate of 2 mm / h until all the melt is crystallized, and then the quartz crucible is moved to the annealing zone (annealing zone temperature is 500 °C) for annealing to form a large-size CoSbS thermoelectric semiconductor crystal.

[0039] Comparative Example 5: Compared with Example 1, the elemental S particles, elemental Sb particles and elemental Co particles in step 1 of Comparative Example 5 are mixed and then placed in a crucible and vacuum-sealed. The elemental S particles are not placed in the lower layer of the metal particles, and the other conditions are the same as in Example 1.

[0040] Comparative Example 6: Compared with Example 2, the elemental S particles, elemental Se particles, elemental Sb particles and elemental Co particles in step 1 of Comparative Example 6 are mixed and then placed in a crucible and vacuum sealed. The elemental S particles are not placed on the top layer of the metal particles, and the other conditions are the same as those in Example 2.

[0041] Comparative Example 7: Compared with Example 1, the swing melting temperature in step 1 of Comparative Example 6 is too low, and the melting swing temperature is 350° C., and the other conditions are the same as those in Example 1.

[0042] Comparative Example 8: Compared with Example 1, the swing melting temperature in step 1 of Comparative Example 6 is too high, and the melting swing temperature is 950° C., and the other conditions are the same as those in Example 1.

[0043] Figure 1 The X-ray diffraction pattern of CoSbS thermoelectric semiconductor crystal obtained in Example 1 is as follows: Figure 1 It can be seen that the grown CoSbS thermoelectric semiconductor crystal is a single phase.

[0044] Figure 2 CoSbS prepared in Example 2 0.85 Se 0.15 Scanning spectrum of thermoelectric semiconductor crystal, from Figure 2 It can be seen that CoSbS 0.85 Se 0.15 The distribution of various elements in the thermoelectric semiconductor crystal is very uniform.

[0045] Figure 3 CoSbS was prepared for Example 2 and Comparative Example 1. 0.85 Se 0.15 The relationship between the thermal conductivity of thermoelectric semiconductor crystals and temperature changes, from Figure 3 It can be seen that Example 2 has a similar thermal conductivity as Comparative Example 1.

[0046] Through the results of Example 1, Comparative Example 2 and Comparative Example 3, it is found that the size of the crucible has an important influence on the melt growth of the CoSbS crystal raw material. If a single-layer quartz crucible is used in Comparative Example 2, the melt will break through the quartz crucible during the melt growth stage, and the melt will flow out, making it impossible to carry out solution growth. If the bottom of the quartz crucible in Comparative Example 3 is flat, too many crystal nuclei will be produced at the bottom of the flat-bottomed crucible, resulting in the crystal growth along multiple crystal nuclei, resulting in the final CoSbS thermoelectric semiconductor crystal having a complex crystal orientation and a low crystal orientation.

[0047] It was found from the results of Example 1 and Comparative Example 4 that the temperature of the melting zone was too low, resulting in the inability of the CoSbS crystal raw material to melt and subsequent melt growth to be performed.

[0048] The sulfur element vaporization loss rate of Example 1, Example 2, Comparative Example 5, Comparative Example 6, Comparative Example 7 and Comparative Example 8 was tested. The testing method was as follows: the crucible containing the CoSbS polycrystalline raw material was broken, the crucible fragments were collected after removing the CoSbS polycrystalline raw material, the crucible fragments were placed in a pure oxygen atmosphere and heated at 1000° C., the generated gas after heating was transferred to nitrogen for cooling, and the mixed gas after cooling was charged into a gas chromatograph for quantitative analysis of the sulfur element, and the vaporization loss rate of the sulfur element was calculated, the sulfur element vaporization loss rate=[1-(total mass of the raw material-mass of the sulfur element attached to the surface of the crucible) / total mass of the raw material]╳100%; the test results are shown in Table 1.

[0049] Table 1 Test results

[0050] As shown in Table 1, by analyzing the sulfur loss rates of Example 1, Example 2, Comparative Example 5, Comparative Example 6, Comparative Example 7 and Comparative Example 8, it is found that the method provided by the present invention can reduce the sulfur loss rate of the prepared CoSbS polycrystalline raw material to 0.002~0.003%. By analyzing the results of Example 1, Example 2, Comparative Example 5 and Comparative Example 6, it is found that in Comparative Examples 5 and 6, the sulfur loss rate of the CoSbS polycrystalline raw material prepared by directly mixing the elemental S particles and other elemental particles and then transferring them into a crucible for melting reaches 0.011~0.012%, which is significantly higher than that of Example 1 and Example 2. By analyzing the results of Example 1 and Comparative Example 8, it is found that the use of an excessively high melting temperature in Comparative Example 8 will cause the sulfur loss rate of the CoSbS polycrystalline raw material to reach 0.021%, which is significantly higher than that of Example 1.

[0051] After analyzing the above results, the present invention believes that elemental sulfur and other raw material elemental particles react and generate sulfides during the melting process. Since the reaction of sulfur and metal to generate sulfides will release a large amount of heat, when the melting temperature is too high, the reaction heat will be transferred to the internal metal, causing the internal metal to melt rapidly, resulting in the collapse of the metal particle structure, and the raw material melt will quickly mix into one. Since the melting process is fast, sulfur and metal will react rapidly and quickly release a large amount of reaction heat. The large amount of reaction heat will cause the sulfur element that has not yet reacted to be vaporized in large quantities, thereby significantly increasing the sulfur element gasification loss rate.

[0052] The raw material particles of the present invention are placed in a special way in the crucible, and the elemental sulfur particles and other raw material elemental particles are stacked in the crucible in sequence, so that the elemental S particles are located in the lower layer of other raw material elemental particles. When heated, the elemental sulfur will first begin to melt to form a melt. At this time, the elemental particles on the upper layer of the elemental sulfur will gradually immerse into the sulfur melt to react with the elemental sulfur to generate sulfide and generate reaction heat. The reaction heat melts the other elemental particles and further enables the elemental sulfur and the metal element to fully react to form sulfide, and will not cause overheating in the melt, thereby avoiding the problem of large-scale sulfur gasification caused by rapid accumulation of reaction heat. Appearance; in addition, the use of single-substance particles can create larger gaps between the raw materials. When the single-substance particles are not immersed in the sulfur melt, the gap structure can block the heat transfer between metals, ensuring that the reaction speed will not be too fast, so that the sulfur element can have sufficient time to react with other raw materials, further inhibiting sulfur vaporization; the melting temperature cannot be too high. Too high a temperature will cause the reaction heat and external heat to exceed the melting temperature of other raw materials, resulting in other raw materials also melting and entering the sulfur melt at the bottom, causing all raw materials to quickly mix into one and cause the reaction heat to accumulate rapidly and cause a large amount of sulfur to vaporize.

[0053] In addition, by analyzing the results of Example 1 and Comparative Example 7, it was found that the polycrystalline material with too low a melting temperature could not effectively react the S element with the metal, and the heat released when forming sulfides was not enough to melt the metal particles, and thus it was impossible to produce high-quality CoSbS polycrystalline raw materials.

[0054] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A large-sized CoSbS-based thermoelectric semiconductor crystal, characterized in that: The large-size CoSbS-based thermoelectric semiconductor crystal is made by a melt growth method using a CoSbS polycrystalline raw material. The CoSbS polycrystalline raw material is made by swing melting single Co particles, single Sb particles, and single S particles at 650-750°C. During the swing melting, the single S particles are placed under the single Co particles and the single Sb particles.

2. The large-sized CoSbS-based thermoelectric semiconductor crystal according to claim 1, characterized in that: The large-size CoSbS-based thermoelectric semiconductor crystal also includes a doping element, which is one of Cu, Zn, Ni and Se elements, and the doping content is 0-0.

2.

3. The large-sized CoSbS-based thermoelectric semiconductor crystal according to claim 1, characterized in that: The large-size CoSbS-based thermoelectric semiconductor crystal has a diameter of 10-40 mm and a length of 5-10 cm.

4. A method for preparing a large-sized CoSbS-based thermoelectric semiconductor crystal according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: placing single S particles at the bottom of the crucible, and then stacking single Co particles and single Sb particles on the upper layer of the single S particles, vacuum sealing the crucible and then swing melting to produce CoSbS polycrystalline raw materials; Step 2: Place the CoSbS polycrystalline raw material in a crucible and seal it in vacuum, place the crucible in a vertical crystal growth device, first place the crucible in the melting zone for melting to form a melt, then place the crucible in the cooling crystallization zone and move it for gradient cooling crystallization, and finally anneal the crucible to form a large-sized CoSbS-based thermoelectric semiconductor crystal.

5. The preparation method according to claim 4, characterized in that: The melting temperature of the swing melting in step 1 is 650-750°C.

6. The preparation method according to claim 4, characterized in that: The swing melting time in step 1 is 0.5~3 h, and the speed is 10~30 r / min.

7. The preparation method according to claim 4, characterized in that: In step 2, the amount of CoSbS polycrystalline raw material used is 20-100 g.

8. The preparation method according to claim 4, characterized in that: The conditions of the melting zone in step 2 are: temperature of 950~1050°C, heating rate of 1~2.5°C / min, and residence time of 8~20 h.

9. The preparation method according to claim 4, characterized in that: The conditions of the cooling crystallization zone in step 2 are: temperature gradient of 15-25 °C / cm, and crucible moving speed of 0.2-3 mm / h.

10. The preparation method according to claim 4, characterized in that: In step 2, the bottom of the crucible is conical, and the taper of the cone is 17-44°; the diameter of the crucible is 10-50 mm, and the length of the crucible is 20-40 cm.

Citation Information

Patent Citations

  • A method for preparing a cubic CoSbS thermoelectric compound

    CN109626446B

  • Method for preparing high-performance CoSb3-based thermoelectric materials by one step

    CN105671344A

  • Preparation method of cubic structure CoSbS thermoelectric compound

    CN109626446A

  • A process for ion implantation activation in a compound semiconductor crystal

    EP0169020A1

  • Method for growing compound single crystal

    JP1987197399A